ANALISIS IMPLEMENTASI DEPOSITO BERJANGKA PADA BANK SYARIAH BERDASARKAN HUKUM EKONOMI SYARIAH - Agus Mulyadi (IAIN Ambon, 2021)
Time deposits are one of the Sharia banking products that are included in the funding category using the Mudharabah agreement. Investors take advantage of the funds they invest in the previously agreed-upon profit sharing method with the bank. But in practice the ratio given by the Islamic bank still refers to the basic interest rate which makes some investors secure the halal ratio. Even though the rukak or not the mudharabah contract is free of interest. So it is necessary to know how to calculate the ratio or percentage of profits made by Islamic banks so that it is clear the legal position of the deposit with the mudharabah agreement. Keywords: Deposits, Mudharabah, and Ratio